The Analysis of Zimbabwe`s informal Sector`s Economic Sustainability Subject to Lockdown Effects - Tarupiwa, Tafadzwa Telmore (iRASD Journal of Economics, 2020)
Zimbabwe`s economic society had been dominated by the informal sector as the main source and substitute for formal employment. It comprises of vendors, crosses border traders, cottage industries, artisanal miners and many others conducting lawful but unregistered economic activities. Given it being seen as a new normal for Zimbabwe`s economic structure, the 2020 national lockdown necessitated the analysis on the economic sustainability of Zimbabwe`s informal sector given the hardship experienced. Applying extensive literature review, content analysis and critical assessment of theory and practice as the methodology, the informal sector is deemed highly unsustainable economically. This paper proposes a total restructuring of Zimbabwe`s sector structure, through the creation of a total development strategy that enables refocusing government expenditure and policy towards realignment of informal structure to formal. Furthermore, this paper advocate for a balanced development strategy, that incorporates all sectors which accelerate growth and a stable formal sector through technological innovations and modernisation such that there is technology transfer to the informal sector, as opposed to arbitraging and vending activities as they are prone to stagnation and vulnerability.